Creative Activation for Community Nutrition Education: Integrating Health Counselling, Culinary Training, and Mural-Based Visual Recall - Otje Herman Wibowo; Marina Wardaya; Pandu Rukmi Utomo; Victor Kurniawan Yuwono (Faculty of Smart Technology and Engineering, Universitas Kristen Maranatha, Bandung, Indonesia, 2026)
This project addresses the stunting problem in Kampung Plampitan by increasing community awareness of the health benefits of tempe, a nutritious and affordable source of plant-based protein. Health and stunting prevention topics were delivered through two main formats: health education presentations and hands-on tempe-based cooking demonstrations. The murals functioned as continuous visual reinforcement, supporting recall of key messages, while the primary educational focus remained on improving nutrition knowledge and practical food preparation skills using tempe. By placing the murals in highly visible public locations, community members were encouraged to reflect on their own practices and share information with others, thereby fostering an ongoing understanding of healthy eating and supporting sustained community-level awareness. Program effectiveness was evaluated using pre- and post-intervention measures of knowledge, attitudes, and practices related to tempe consumption, complemented by qualitative observations during implementation. The results indicated increased awareness of tempe’s health benefits, more positive attitudes toward its consumption, and stronger intentions to adopt healthier cooking and eating behaviours. The murals were rated positively for their visual appeal, clarity, and effectiveness in reinforcing key nutrition messages related to balanced diets and stunting prevention. These findings suggest that mural-based visual recall, when integrated into experiential and educational interventions, offers a cost-efficient and scalable approach to community nutrition communication.